Diallel inheritance of relevant traints in cassava (Manihot esculenta Crantz) adapted to acid-soil savannas - Calle, F.; Pérez Velásquez, Juan Carlos; Gaitan, W; Morante, N; Ceballos, H.; Llano Rodríguez, Germán Alberto; Álvarez, E. (2005)
There is a limited knowledge on the inheritance of traits with agronomic relevance in cassava. A diallel study among 10 parental clones was conducted in the acid-soils environment in the eastern savannas of Colombia. Thirty clones were obtained for each F1 cross. Each clone was represented by six plants, which were distributed in three replications at two locations. Therefore, the same 30 genotypes of each F1 cross were planted in the three replications at the two locations. Analysis of variance suggested significant effects for five of the six variables analyzed (harvest index, dry matter content, height of first branching, reaction to super elongation disease, and plant type scores). Fresh root yield showed strong genotype × environment interaction and differences between crosses reached statistical significance in only one of the two environments analyzed. General and specific combining ability effects and their interaction with the environment were significant for most of the variables as well. Results suggested that dominance plays an important role particularly in the cases of fresh root yield and harvest index.